A Study on Breast-feeding Self-Efficacy and Its Associated Factors Among Mothers - Ritu Prajapati; Nidhi Sagar; Mamta (International Journal of Midwifery Nursing And Practices, 2023)
Introduction: The process through which a kid is fed human breast milk is known as breastfeeding. Breastfeeding has a significant impact on disease prevention and health promotion. It helps to increase bonding with baby and mother. Oestrogen, progesterone, prolactin, and oxytocin are the four primary hormones that contribute to the production of breastmilk. A modifiable element that can improve breastfeeding success and duration is breastfeeding self-efficacy. Aim: To evaluate mothers' self-efficacy for breastfeeding and the aspects that are related to it in order to advance both the mother's and the child's health. Methodology: A non-experimental exploratory research design and a quantitative research approach were employed with 250 mothers who had babies between the ages of 0 and 6 months and who visited the paediatric OPD of the DMCH in Ludhiana, Punjab, as the sample. Non-probability purposive sampling was used to gather the data. The breast-feeding self-efficacy of mothers was evaluated using a structured checklist of 27 items and the 14-item breast-feeding self-efficacy scale created by Dennis (1999). The interview technique was used to acquire quantitative data. Data were tabulated, and descriptive and inferential statistics were used for the analysis. (Using SPSS,20). Result: According to the survey, more than half of the moms (71%) were between the ages of 25 and 35, and 81.2% had graduated from college. 21.2% were working, 93.6% were living in joint family, 95.6% live with in-laws, 57.6% were vegetarian. Overall, 90.4% mothers had above average level of breast-feeding self-efficacy followed by 9.2% with average breast-feeding self-efficacy while (0.4%) mothers had below breast-feeding self-efficacy. The factors associated with breast-feeding self-efficacy were emotional changes during feed, feeling relief from engorgement, inadequate sleep, back and neck pain, fatigue and stress related to work load. Conclusion: The current study found that the majority of moms were confident in their ability to breastfeed. Breast-feeding self-efficacy was good among those who already had experience. Parity, number of live birth, type of delivery were found to be significantly associated with breast-feeding self-efficacy.
Keywords: Breast-feeding self-efficacy and associated factors